The billionaire behind the headlines - Stewart, Rachael (Sydney, NSW : Harlequin Mills & Boon, 2022)
Can a playboy billionaire...capture her heart? Bree has escaped the big city to heal her heart in a village bakery. But when notorious billionaire Theo walks through the door, emotionally guarded Bree discovers it's not just her toffee pudding that's hot and sweet! The man behind the headlines is charming but intriguingly cynical about love. Accepting his invitation to Paris could be a mistake - or the best decision she's ever made....
Title from title screen.
General.
Mode of Access: Available online.
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Electronic books; Romance fiction